Universal pathogenicity of authoritarian focus in pedagogues’ professional communications - Dziuba, Tetiana; Zvyagolskaya, Iryna (Social Welfare: Interdisciplinary Approach, 2018)
The paper examines the specificity of authoritarian focus in pedagogues’ professional communications, which can be the source of psychological traumatisation, provoke the development of health deviations among the participants of education process, causing the emergence of functional and chronicle diseases. It is observed, that the authoritarian focus under the conditions of stressful professional reality creates “chronicle” psycho-traumatic atmosphere in professional communications of employee and can provoke emergence of negative emotional experiences (psychogeneses). Important aspect of examined problem is the fact, that authoritarian interactions in activities (learning, professional) can be the reason for emergence of children’s didactic geneses and development of neuroses. Pedagogue’s sensibility to the demonstrations of authoritarianism points out the undeveloped readiness to build effective professional pedagogical communications, which can become the source of traumatisation and aggravation of pedagogue’s own didactopathy. The results of empirical study of influence of factor “authoritarianism” on the pedagogues’ occupational health with the author’s technique “Occupational health” are presented. The observed correlation tendencies indicate the phenomenon of authoritarian focus in pedagogue’s professional communications, that’s why the authoritarianism syndrome can be the serious barrier for the progressive professional development of the specialist, the ruining factor to the professional communications, which influence the psychological well being and health state of employee. Pedagogue with authoritarian focus of world perception is characterized by the behaviour, which is based on the belief, that using of own status and authority provides the sustaining of hierarchical subordination, control, security and professional stability.